Use of methotrexate as a predictor for fetal malformations (Research, Society and Development, 2021)
Objective: To review the literature on fetal malformations caused by the use of methotrexate during pregnancy. Methodology: This is a narrative review of literature, including all articles that addressed the topic, in the last ten years. Results and Discussion: For the pregnant woman's prenatal care to be smooth and without major complications, some care must be followed to the letter and, among them, the use of medications, which can either cause complications or be incompatible with the life of the mother. mother and baby, the use even before the start of pregnancy can compromise the pregnancy. Thus, it is necessary to quickly observe and conduct the multidisciplinary professionals who accompany the pregnant woman. Methotrexate (MTX) is a safe and effective treatment for ectopic pregnancy without the possibility of surgical risks. The doctor acts by directly attacking the cause of the pathology and not the embryo, but causing its death. In these cases, drug intervention is pointed out by some as an indirect abortion in view of this, an unethical act. Methotrexate is a medication with a potent teratogenic agent in humans, which makes it an inducer of an increased risk of miscarriages, intrauterine growth restriction and congenital malformations in case of exposure during pregnancy. Final Considerations: In light of the above, you see It should be noted that the use of methotrexate during pregnancy directly impacts the health of the mother and fetus, so that it can cause cranial and cardiac malformations that can lead to death.